Vascular endothelial growth factor-expressing neural stem cell for the treatment of neuropathic pain. Issue 7 (6th May 2015) - Lee, Hye-Lan; Oh, Jinsoo; Yun, Yeomin; Lee, Hye Yeong; You, Youngsang; Che, Lihua; Lee, Minhyung; Kim, Keung Nyun; Ha, Yoon
<x xml:space="preserve">Abstract</x> Previously, we determined that vascular endothelial growth factor (VEGF) improves the survival of neural stem cells (NSCs) transplanted into an ischemic environment and effectively enhances angiogenesis. Here, we applied NSCs expressing VEGF (SV-VEGF-NSCs) to treat neuropathic pain. In this study, our goal was to verify the therapeutic effect of SV-VEGF-NSCs by transplanting the cells in a sciatic nerve injury model. We compared the amount of VEGF secreted from DsRed-NSCs (control) or SV-VEGF-NSCs and observed that SV-VEGF-NSCs have a much higher expression level of VEGF. We next investigated whether transplantation with SV-VEGF-NSCs aids functional recovery and pain reduction. We confirmed that transplantation with SV-VEGF-NSCs enhances functional recovery, pain reduction, and remyelination as well as the number of blood vessels compared with the control groups. Our results show that VEGF aids functional recovery and pain reduction in a sciatic nerve injury model.